2018
DOI: 10.1159/000481818
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Efficacy and Safety of the Novel Medical Adhesive, MAR VIVO-107, in a Rabbit Liver Resection Model

Abstract: Background: Topical hemostatic agents are useful when hepatic hemorrhage is difficult to control. The aim of this study was to evaluate the hemostatic efficacy and safety of a biodegradable polyurethane-based adhesive, MAR VIVO-107 (MAR), in comparison with a clinically used fibrin glue. Methods: Thirty female New Zealand white rabbits were randomly assigned to 3 study groups as follows: MAR (n = 10), fibrin glue (n = 10), and saline groups (n = 10). After standardized partial liver resection was performed, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The tissue adhesive VIVO showed good adhesion in mass bleeding and wet tissues 18 , 19 . In addition, our results show that VIVO has sufficient tensile strength 1.33 ± 0.46 [N] and burst pressure 299 ± 4.47 [mmHg], to adhere adequately to wet tissue, making it a suitable material for seamless vascular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue adhesive VIVO showed good adhesion in mass bleeding and wet tissues 18 , 19 . In addition, our results show that VIVO has sufficient tensile strength 1.33 ± 0.46 [N] and burst pressure 299 ± 4.47 [mmHg], to adhere adequately to wet tissue, making it a suitable material for seamless vascular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of adhesives on wet tissues is considered particularly challenging 17 . In contrast, VIVO has shown significant hemostatic results in mass bleeding porcine liver resection models 18 and long-term rabbit mass bleeding liver resection models 19 . Both investigations were conducted in liver tissue that was bleeding heavily and moist.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies have reported the use of the novel medical adhesive VIVO based on polyurethane/urea technology [10, 11]. VIVO is composed of 2 ingredients: an isocyanate-functionalized prepolymer as an adhesive agent and a curing agent mixture mainly based on amine-functionalized aspartic acid ester(s) and filling agent(s) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…VIVO is composed of 2 ingredients: an isocyanate-functionalized prepolymer as an adhesive agent and a curing agent mixture mainly based on amine-functionalized aspartic acid ester(s) and filling agent(s) (Fig. 1) [10][11][12]. A static mixing unit was used to mix the 2 components, which could easily be applied to the wound surface.…”
Section: Novel Medical Adhesivementioning
confidence: 99%
See 1 more Smart Citation